The influence of Manichaean and Nestorian religions in the settled life of the ancient Turks - Kairken, Т.З.; Alkeyeva, Д.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The Turkic peoples of Central Asia have long resided at the nexus of Eastern and Western cultures, fusing urban and steppe civilizations with dexterity. Their spiritual life was also strongly influenced by Indian and Persian culture. Indian and Persian cultures first spread to settlements in the Maurennahr and Tarim Basin, and then to small towns and settlements in the foothills of the Semirechye and Erenkabyrga (Tien Shan) mountains. Therefore, Central Asia has become a zone of interweaving of all cultures of the world, including all religions. Different religions spread not only to settled regions, but also to steppes, which led a nomadic lifestyle. In the regions where nomadic Turks lived, small settlements and places of worship were built. Back then, nomads showed respect to anyone who held a religious role. At the same time, for a long time in Central Asia and East Turkestan and neighbouring regions, various cultures and spiritual values of mankind competed closely. This suggests that Central Asia, East Turkestan, and Central Mongolia have evolved geographically as essential components of human civilization since the first century AD. The article discusses how the Manichaean and Nestorian religions, which were prevalent in this area prior to Islam, were viewed by the Turkic people living there and how they fit in with the natural surroundings, social structure, governmental power, etc. The “Yangzhou” and “Monument of the Nine Uighur Khagans” are examples of the widespread adoption of Manichaean and Nestorian religions among the Turks. A linguistic and source examination of these monuments was done.